The life and careers of John Philby Government of India until it joined the campaign to occupy Iraq. 1914 (Journal of the College of Basic Education, 2023)
This study will try to reveal a British personality who contributed in different roles in the realities.history that the Arabian Peninsula in general and the Kingdom of Saudi Arabia went through in particular, in light of the intensification ofThe Ottoman-British competition for control of the region, as well as the escalation of the struggle between the leaders ofthe Arabian Peninsula, in the attempt of each party to achieve its objectives at the expense of the other party, whileBritain is watching the events closely and is exerting its efforts through its representatives in the Gulf and the Arabian Peninsula, to perpetuate the situation.